Research on the Evaluation of Urban Logistics Innovation Capacity under the Background of New Qualitative Productive Forces - Liu, Xinyu (International Journal of Social Sciences and Public Administration, 2024)
Based on the development background of new qualitative productive forces, this paper constructs an innovation capacity indicator system from five aspects: regional economic capacity, logistics operation capacity, logistics infrastructure, innovation drive capacity, and green development capacity. It employs the factor analysis method to conduct a comprehensive quantitative evaluation and ranking of the logistics innovation capacity of 18 cities in Henan Province. Additionally, using the systematic cluster analysis method, the logistics innovation capacity of each city is classified into three gradients. The research conclusions indicate significant differences in logistics innovation capacity among the 18 cities in Henan Province. Furthermore, suggestions are proposed in terms of scientific and technological talents and investment, logistics infrastructure equipment construction, and green logistics to promote the regional synergy of logistics in various cities in Henan Province and achieve innovative development.